An Overview of Methods and Tools for Transfection of Eukaryotic Cells in vitro - Fus-Kujawa, Agnieszka; Prus, Pawel; Bajdak-Rusinek, Karolina; Teper, Paulina; Gawron, Katarzyna; Kowalczuk, Agnieszka; Sieron, Aleksander L. (Frontiers in Bioengineering and Biotechnology, 2021)
Transfection allows to introduce foreign nucleic acids into cells. Their successful delivery is influenced by various factors such as type of cells, cell culture passage number and presence or absence of serum in the cell culture medium during transfection. To obtain high efficiency of transfection, crucial are quality and quantity of the nucleic acids. In past, many ways of introducing nucleic acids into cells have been developed. Those methods utilized as carriers of nucleic acids, viruses, non-viral carriers, and physical factors. Many types of nanoparticles have been successfully tested as non-viral carriers of nucleic acids. The most common were cationic polymers that have been shown as molecules, soluble in aqueous solution. Chemical structures of such particles could be modified, therefore, they were also less immunogenic and less toxic. Additionally, they were perfect candidates for nucleic acids delivery to cells. This work is an overview presenting various methods and systems for eukaryotic cells transfection. It discusses pros and cons of the presented delivery systems and transfection methods.